2021
DOI: 10.3390/plants10030569
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Taxanes: Focus on Their Bioactivity, Delivery and Combination Therapy

Abstract: Taxanes, mainly paclitaxel and docetaxel, the microtubule stabilizers, have been well known for being the first-line therapy for breast cancer for more than the last thirty years. Moreover, they have been also used for the treatment of ovarian, hormone-refractory prostate, head and neck, and non-small cell lung carcinomas. Even though paclitaxel and docetaxel significantly enhance the overall survival rate of cancer patients, there are some limitations of their use, such as very poor water solubility and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 175 publications
0
50
0
1
Order By: Relevance
“…Currently, they are being clinically tested mostly against cancer, since by triggering the NKA signalosome, CGs can induce apoptosis. However, what makes CGs exceptional among other anticancer drug candidates such as antimitotics [ 82 , 83 ]? In this review article, we showed that the great advantage of CGs in anticancer treatment is the induction of ICD.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, they are being clinically tested mostly against cancer, since by triggering the NKA signalosome, CGs can induce apoptosis. However, what makes CGs exceptional among other anticancer drug candidates such as antimitotics [ 82 , 83 ]? In this review article, we showed that the great advantage of CGs in anticancer treatment is the induction of ICD.…”
Section: Discussionmentioning
confidence: 99%
“…The role of taxanes in monochemotherapy or in combination with other active agents has suggested their potential therapeutic impact on the treatment of patients with early BC. Recent studies in the adjuvant setting have shown that taxanes, used individually or in combinations, possess the capability to induce significant improvement in terms of survival of BC patients [ 130 , 131 ].…”
Section: “Saha Et Al” and Breast Cancermentioning
confidence: 99%
“…In recent years, natural products have aroused people’s interest in the development of new anticancer therapeutic drugs [ 61 , 62 , 63 ], because most of them show good potential of medicinal significance, which can be used as alternative drugs for the treatment of various diseases (including cancer) with few side effects relatively [ 64 , 65 ]. TDA is a newly discovered octahydronaphthalene derivative, isolated from the secondary metabolites of plant endophytic fungi, and has shown anticancer activity in a variety of cancers [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%